PERENCANAAN SISTEM PLUMBING AIR BERSIH DAN AIR KOTOR PADA BANGUNAN RUMAH 2 LANTAI DI AMBUNTEN, SUMENEP, MADURA - Alfan Sudeis Al Burhani; Daffa Zahid Fawwas; David Christiandayinta Anggraini; Eko Suwarno; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The city of Sumenep is located in the eastern part of Madura Island, where there is a great deal of land with high potential for residential development. Plumbing system design is a key factor in ensuring efficient water use in residential buildings, particularly multi-story structures. This study aims to design a clean and wastewater plumbing system for a two-story house located in Ambunten, Sumenep, Madura. The study adheres to the Indonesian National Standards (SNI). The research method employed is a literature review based on the Indonesian National Standards (SNI). The results of the clean water demand planning are influenced by the number of occupants and the activities of each individual, with an average daily demand of 60–90 liters per person. The water distribution system uses a combined pump and storage tank design to ensure stable water pressure on every floor.